Mesenchymal Stem Cell Exosomal miR-146a Mediates the Regulation of the TLR4/MyD88/NF-κB Signaling Pathway in Inflammation due to Diabetic Retinopathy. (18th June 2022) - Gu, Cao; Zhang, Hongjun; Zhao, Shaofei; He, Daotong; Gao, Yu
Abstract : Diabetic retinopathy (DR) is the main cause of vision loss in diabetic patients, which cannot be completely resolved by typical blood sugar control. Inflammation influences the development of DR, so reducing the inflammatory response in DR patients is crucial to the prevention of DR. Therefore, we explored the regulatory effect of bone marrow mesenchymal stem cell (BMSC) exosomes on inflammation in DR mice. In order to analyze the mechanism of action, we used BMSC exosomal miR-146a to treat microglias in DR mice to observe cellular changes and expression of inflammatory factors. It was found that BMSC exosomal miR-146a reduced the levels of proliferating cell antigen and B-cell lymphoma-2 in microglias of DR mice and increased Bcl-2-related X with cysteine aspartic protease-3. By analyzing the expression of inflammatory factors, we found that BMSC exosomal miR-146a reduced the levels of TNF- α, IL-1 β, and IL-6, which suggested that miR-146a can alleviate inflammation in DR mice. Further exploration found that miR-146a reduced the activity of TLR4 and increased the activity of MyD88 and NF- κ B. Furthermore, the overexpression of TLR4 reversed the effects of miR-146a on the proliferation, apoptosis, and inflammation of microglias. Our study demonstrated that BMSC exosomal miR-146a can regulate the inflammatory response of DR by mediating the TLR4/MyD88/NF- κ B pathway, providing an experimental basis for the prevention and treatment of DR.